The Role of the Steelworker Occupational Community in the Internalization of Industrial Restructuring: The 'Layering Up' of Collective Proximal and Distal Experiences. (October 2019) - McLachlan, Christopher J; MacKenzie, Robert; Greenwood, Ian
This article explores the relationship between occupational community and restructuring at a UK steelworks. Through historic and contemporary experiences, restructuring has become an internalized feature of the steelworker identity. Zittoun and Gillespie's framework of proximal and distal experiences is adapted to analyse the internalization process. The article argues that experiential resources associated with restructuring are transmitted via the occupational community, forming a part of a collective memory of workplace change. These experiences relate to the historical precedence of restructuring, the role of trade unions in accepting the inevitability of downsizing and prior personal and vicarious experiences of redundancy. The findings build on debates around the determinants of an occupational community, highlighting the role of 'marginality' and how experiences of restructuring bind steelworkers to a broader community of fate.